الخدمات التعليمية المقدمة لطلاب الانتساب المطور بجامعة الإمام محمد بن سعود الإسلامية: دراسة تقويمية تطويرية - الرشود، عبدالله بن محمد بن راشد (جامعة الإمام محمد بن سعود الإسلامية, 2017)
هدفت هذه الدراسة إلى تقويم الخدمات التعليمية المقدمة لطلاب الانتساب المطور بجامعة الإمام محمد ابن سعود الإسلامية، مع بيان أهم السبل لتطويرها، وقد استخدم الباحث لتحقيق هذا الهدف منهج البحث الوصفي بنوعيه الوثائقي والمسحي مستخدماً أداة الاستبانة في الدراسة المسحية، وتكونت عينة الدراسة من (310) من الطلاب والطالبات. وقد أسفرت الدراسة عن عدد من النتائج أهمها: - تقوم عمادة التعلم الإلكتروني والتعليم عن بعد بعدد من المهام والخدمات التعليمية تجاوزت خمس عشرة خدمة تعليمية أساسية يتفرع منها العديد من المهام والخدمات التفصيلية. - بلغ عدد اللقاءات الحية في الفصل الثاني من العام الجامعي 1433/1434ه (3899) لقاءً حياً لـ(302) مقرر دراسي ساند فيها (268) من أعضاء هيئة التدريس بالجامعة. - أفراد عينة الدراسة راضون عن الخدمات التعليمية بدرجة عالية حيث بلغ المتوسط الحسابي الموزون لإجاباتهم (3.55 من 5)، كما أنهم راضون بدرجة عالية جداً عن اثنتين من الخدمات التعليمية، وهي: تقديم إفادة القبول لمن يحتاجها من الطلاب، وطريقة تسجيل الطالب للمقررات بداية كل فصل دراسي. - أفراد عينة الدراسة راضون بدرجة عالية عن سبع عشرة خدمة تعليمية، وبدرجة متوسطة عن تسع خدمات تعليمية أقلها رضاً الخدمات المتعلقة بالتكليفات الذاتية والتطبيق الميداني. - وافق أفراد العينة على مقترحات تطوير الخدمات التعليمية بدرجة قوية، بمتوسط بلغ (3.93 من 5). - وافق أفراد العينة بدرجة قوية جداً على ستة من السبل المقترحة لتطوير الخدمات التعليمية، منها: إشعار الطالب بنتيجته الفصلية برسالة عبر الجوال أو البريد الإلكتروني، وإمكانية تشغيل المحاضرات الحية من جميع الأجهزة الذكية، وزيادة عدد المقررات المعتمدة في الفصل الصيفي لتشمل جميع المستويات. - عدم وجود فروق دالة إحصائياً في استجابات أفراد العينة تبعا لمتغيري المستوى الدراسي والجنس. - أما متغير التخصص الدراسي فقد أظهرت النتائج وجود فروق دالة إحصائيا في استجابات أفراد العينة على عبارات الاستبانة مجملة لصالح طلاب قسم الشريعة، وفي المحور الأول لصالح طلاب قسم الدعوة، أما المحور الثاني المتعلق بأساليب تطوير الخدمات التعليمية فلا يوجد في استجابات أفراد العينة فروق ذات دلالة إحصائية بينها. وبناءً على نتائج الدراسة قدم الباحث عدداً من التوصيات العلمية أهمها: - ضرورة المحافظة على مستوى الأداء المقدم من العمادة للطلاب والطالبات في مجال الخدمات التعليمية التي حصلت على درجة رضا عالية وعالية جداً، وعددها (19) خدمة تعليمية. - العمل على تطوير الخدمات التعليمية التي لم تحصل على درجة رضا عالية وهي (9) خدمات تعليمية. - العمل على تفعيل سبل تطوير الخدمات التعليمية التي حصلت على تأييد وموافقة أفراد عينة الدراسة.
This study aims to evaluate the educational services provided to students of the enhanced Part-Time Program at Al-Imam Muhammed Ibn Saud Islamic University highlighting the most important means of developing these services. The researcher uses the descriptive documentary method as well as the descriptive survey method using the questionnaire as instrument in the survey study. The study sample consists of (310) male and female students. The study reveals a number of findings. First, The Deanship of E-Learning and Distance Education undertakes a number of tasks and educational services amounting to more than 15 basic educational services which include several secondary tasks and services. Second, the number of live sessions was 3899 during the second semester of the academic year 1433/1434 AH for 302 courses, run by 268 faculty. Third, the study sample participants are highly satisfied with the educational services as the weighted arithmetic mean of their responses shows and which is 3.55 out of 5.0. They are also highly satisfied with two educational services; namely, providing a statement of acceptance for students who need it, and the way a student registers for courses at the start of a new academic term. Fourth, the study sample participants are highly satisfied with 17 educational services, moderately satisfied with 9, and least satisfied with the services concerning self-assignments and field training. Fifth, the study sample participants strongly agree to the proposals for developing educational services, with an average of 3.93 out of 5.0. Sixth, the study sample participants strongly agree to 6 of the proposed means to develop educational services, including: notifying students of their mid-term results via SMS or e-mail, possibility of running live lectures from all smart devices, and increasing the number of approved courses in the summer term to include all levels. Seventh, there are no statistically significant differences in the responses of the sample participants according to the variables of level and gender. Eighth, there are statistically significant differences in the responses of the sample participants in regards to the variable of specialization in favor of the students of Shari'a College. The first theme is in favor of the students of Da'wah College, whereas there are no statistically significant differences in the responses of the sample study regarding the second theme concerning the means of developing educational services. On the basis of these findings, the researcher presents a number of academic recommendations. The most significant of which is the need to maintain the performance level provided by the Dean ship for male and female students in the area of educational services, which are 19, that have had high and very high satisfaction levels. Second, developing the 9 educational services that have not received a high satisfaction level. Finally, activating ways of developing educational services that received the support and approval of the sample population of the study.
Keywords: التخطيط التربوي -- الخدمات التعليمية -- التعليم عن بعد -- طلبة الجامعات -- التعليم العالي -- السعودية